EFFECTIVENESS OF Beauveria bassiana AGAINST Coptotermes curvignathus - Dewi Ramdhania; Noor Farikhah Haneda; Achmad . (Jurnal Silvikultur Tropika, 2016)
Termites are important pests to human life which can cause severe economic loss in Indonesia. Termites are not only attacking the wood products, but also the living plants with wide host distribution. Implementation of biological agents for termites control is one way to reduce the implementation of synthetic termiticide since it is considered to be more environmentally friendly and doesn’t cause resistance to termites. This research aimed to analyze the effectiveness of conidial density levels of Beauveria bassiana from various media types against Coptotermes curvignathus mortality. The research was designed using factorial completely randomized design by combining media types with conidial density levels. B. bassiana suspensions were made from three types of liquid media consist of Potato Dextrose Broth (PDB), Malt Extract Broth (MEB) and Sabouraud Dextrose Broth with Yeast Extract (SDBY). The suspension with density of 108, 106, and 104 conidia ml-1 from PDB, MEB, and SDBY media were applied to Coptotermes curvignathus. The results showed that all types of nutrients sources (PDB, MEB and SDBY) did not affect the virulence of B. bassiana conidial suspensions against C. curvignathus mortality. Nevertheless, C. curvignathus mortality were affected by the differences of conidial density levels from B. bassiana suspension.Key words: Beauveria bassiana, conidial density, media, mortality